An integrated accountability reporting model of non-profit organisations (NPOs) / Saunah Zainon ... [et al.] - Zainon, Saunah; Bakar, Ahmad Naqiyuddin; Abu Bakar, Nor Fauziah; Ahmad, Badly Esham; Abdul Razak, Rosnani (UiTM Cawangan Johor, 2020)
Non-Profit Organisations (NPOs) have showcased unique features in serving important social missions. In addition, they also offer accounting services at a lower cost than the government or the private sector. However, questions have been raised as to whether the performance measurement used by the government or the private sector is appropriate and applicable to the NPOs. This article underlies a conceptual framework for performance indicator in developing an Integrated Accountability Reporting Model of NPOs. Four components were found to be the essential elements of an Integrated Accountability Reporting for NPOs namely Financial Information, Governance Information, Accountability and Transparency. Integration of these four elements serves as the fundamental aspects of integrated reporting. Based on mandatory and voluntary sources of information, this integrated reporting can be developed for the benefits of NPOs. This paper contributes to the NPO accountability literature by: first, developing a framework of NPO accountability through public discourse using the ethical model of principal-agent theory; and second, advancing the understanding of the accountability reporting of NPOs in Malaysia.